2020
DOI: 10.33086/bfj.v5i2.1788
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Work Overload terhadap Nurse Performance dengan Burnout sebagai Variabel Intervening di Rumah Sakit X Surabaya

Abstract: Job stress is a serious phenomenon that refers to workplace characteristics that threaten workers. Nursing has been identified as a job that has high stress level. Nursalam (2011) states that nurses who are given excessive workload can have an impact on burnout. Burnout occurs when people feel that the resources they value are threatened, they try to maintain those resources (Maslach and Leiter, 2016). Burnout can result in decreased nurse performance/Burnout can cause decreasing of nurse performance. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
3
0
1
Order By: Relevance
“…According to a study by Ruga et al (2022) on 84 inpatient service nurses in Bhakti Asih General Hospital Tangerang show that there is a relationship between physical and mental workload on nurse performance. Similar findings were found in a study by Pamungkas and Sridadi (2020), which concluded that burnout had a significant impact on nurse performance. H2 : Burnout has a significant negative effect on the performance of nurses.…”
Section: Burnout and Nurse Performancesupporting
confidence: 89%
See 3 more Smart Citations
“…According to a study by Ruga et al (2022) on 84 inpatient service nurses in Bhakti Asih General Hospital Tangerang show that there is a relationship between physical and mental workload on nurse performance. Similar findings were found in a study by Pamungkas and Sridadi (2020), which concluded that burnout had a significant impact on nurse performance. H2 : Burnout has a significant negative effect on the performance of nurses.…”
Section: Burnout and Nurse Performancesupporting
confidence: 89%
“…The factors that determine the workload are organizational elements, cultural norms, excessive development of information technology, and commitments outside work, such as family commitments (Kuschel, 2015). A study by Pamungkas and Sridadi (2020) on 40 low -care inpatient service nurses in X Hospital Surabaya showed that there was a significant negative effect between work overload and nurse performance directly or indirectly. Additionally, the results of a study by Van Bogaert et al (2013) showed a significant relation between workload and quality of care.…”
Section: Hypothesis Development Workload and Nurse Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Perkembangan dunia usaha yang pesat menghadirkan tantangan yang unik bagi para pebisnis untuk saling bersaing, termasuk di bidang kesehatan. Tantangan bagi industri kesehatan untuk lebih meningkatkan kualitas layanan agar pelaku ekonomi seperti rumah sakit dapat memberikan kinerja perusahaan yang unggul [1]. Ada unsur-unsur yang berperan dalam menunjang fungsi operasional pada rumah sakit, namun salah satunya yang terpenting adalah sumber daya manusia yang dianggap sebagai aset perusahaan dan memiliki peranan penting dalam kegiatan perusahaan.…”
Section: Pendahuluanunclassified